Late outcomes of valve-in-valve transcatheter aortic valve implantation versus re-replacement: Meta-analysis of reconstructed time-to-event data. (1st January 2023) - Sá, Michel Pompeu; Van den Eynde, Jef; Simonato, Matheus; Hirji, Sameer; Erten, Ozgun; Jacquemyn, Xander; Tasoudis, Panagiotis; Dokollari, Alexander; Sicouri, Serge; Weymann, Alexander; Ruhparwar, Arjang; Arora, Rakesh; et al.
Abstract: Aims: To evaluate all-cause mortality in ViV-TAVI versus redo SAVR in patients with failed bioprostheses. Methods: Study-level meta-analysis of reconstructed time-to-event data from Kaplan-Meier curves of non-randomized studies published by September 30, 2021. Results: Ten studies met our eligibility criteria and included a total of 3345 patients (1676 patients underwent ViV-TAVI and 1669 patients underwent redo SAVR). Pooling all the studies, ViV-TAVI showed a lower risk of all-cause mortality in the first 44 days [hazard ratio (HR) 0.67, 95% confidence interval (CI) 0.49–0.93, P  = 0.017], with an HR reversal after 197 days favoring redo SAVR (HR 1.53; 95% CI 1.22–1.93; P  < 0.001). Pooling only the matched populations (1143 pairs), ViV-TAVI showed a lower risk of all-cause mortality in the first 55 days [hazard ratio (HR) 0.63, 95% confidence interval (CI) 0.45–0.89, P  < 0.001], with a reversal HR after 212 days favoring redo SAVR (HR 1.57; 95% CI 1.22–2.03; P  < 0.001). The Cox regression model showed a statistically significant association of prosthesis-patient mismatch (PPM) with all-cause mortality during follow-up for ViV-TAVI (HR 1.03 per percentage increase in the study- and treatment arm-level proportion of PPM, 95% 1.02–1.05, P < 0.001). Conclusion: ViV-TAVI is associated with a strong protective effect immediately after the procedure in comparison with redo SAVR, however, this initial advantage reverses over time and redo SAVR seems to be a protective factor for all-cause mortality after 6 months. Considering that these results are the fruit of pooling data from observational studies, they should be interpreted with caution and trials are warranted. Graphical abstract: Unlabelled Image Highlights: Structural valve degeneration of bioprosthetic heart valves is a concerning issue. Redo surgical intervention is burdened by higher risk of death especially immediately after the procedure. ViV-TAVI offers an excellent alternative to treat patients with failed bioprostheses, however, redo surgical intervention is associated with better survival over time. Prosthesis-patient mismatch may play a major role in this scenario.